Students’ Perception Towards The Use of Kahoot in Vocabulary Learning - Putera Kamal, Akbar Newton; Utami, Praditya Putri; Kamil, Acep Bahrum (IKIP Siliwangi, 2025)
This study investigates students’ perceptions toward the use of Kahoot! in vocabulary learning at the junior high school level. The research employed a qualitative case study approach involving six ninth-grade students at SMPN 5 Tambun Selatan. Data were collected through observation and semi-structured interviews. The findings reveal that students perceive Kahoot! as a fun, engaging, and motivating tool that enhances vocabulary learning. They found it easier to understand and memorize new words through visual aids, contextual questions, and interactive features. Additionally, the gamified elements of Kahoot!, such as quizzes, scores, and time limits, fostered a more dynamic and competitive learning environment. However, students also reported technical challenges, including unstable internet connections and discomfort with the limited response time. Despite these issues, the overall perception of Kahoot! was positive, indicating its potential to improve vocabulary acquisition and student engagement. The study recommends further research on the long-term effects of gamified learning and comparisons with other platforms.